The Complex Interplay of Segmental and Suprasegmental Features in English Phonology: An Advanced Study - Tria Arini; Annisa Putri Dinata; Muhammad Hasan Agara S; Yani Lubis (Lembaga Pengembangan Kinerja Dosen, 2024)
The study titled